2015
DOI: 10.2174/1874285801509010084
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Temperature and pH on the Activities of Catechol 2,3-dioxygenase Obtained from Crude Oil Contaminated Soil in Ilaje, Ondo State, Nigeria

Abstract: Enrichment technique was employed for the isolation of the crude oil degrading bacteria. The isolated bacteria were screened for their degradative ability and the best degrading bacteria were selected based on their growth. Specific activities of Catechol-2,3-dioxygenase and effects of temperature and pH and their stabilities on the enzyme relative activities were observed. Bacteria isolated from the soil sample include; Bacillus cereus, B. amyloliquficiens, B. firmus, Acinetobacter calcoaceticus, Pseudomonas … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…Petroleum has been publicized as the most terrestrial pollutant [27] and its presence has been stated to change the community structure of pristine soil bacterial in both population and genetic-enzyme process for degradation of hydrocarbon pollutant [28]. The work of several researchers has confirmed that bacterial isolated from hydrocarbon impacted soil have geneencoded with hydrocarbon-degrading enzymes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Petroleum has been publicized as the most terrestrial pollutant [27] and its presence has been stated to change the community structure of pristine soil bacterial in both population and genetic-enzyme process for degradation of hydrocarbon pollutant [28]. The work of several researchers has confirmed that bacterial isolated from hydrocarbon impacted soil have geneencoded with hydrocarbon-degrading enzymes.…”
Section: Discussionmentioning
confidence: 99%
“…The variations in structural conformations of this enzyme and its synthesis mechanisms may vary among isolates. Olukunle et al [28] studied the impact of temperature on C23O activity and reported temperature to act as a promoter of C23O activity with the enzyme to be stable at 30-40°C. This study was carried out in the temperature range of 30-37°C.…”
Section: Discussionmentioning
confidence: 99%
“…A corresponding 5ml aliquot sample was collected for 1ml serial dilution viable plate count and a corresponding daily reading of pH was taken and recorded. All experiments were performed in duplicate ( Olukunle et al , 2015 ; Dilmi et al , 2017 ). The total viable plate count versus incubation time for each bacterial isolates were plotted into growth model curve, and using the first-order growth rate equation, the growth kinetic parameters such as specific growth rate were calculated.…”
Section: Methodsmentioning
confidence: 99%
“…The preference for complex organic nitrogen sources such as yeast extract and peptone for catecholase production from various Pseudomonas sp. like P. fragi, P. fluorescens BW 96 has also been observed Olukunle and workers [16].…”
Section: Effect Of Nitrogen Sourcementioning
confidence: 62%